2021
DOI: 10.1111/jcpp.13474
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index and internalizing symptoms from early childhood through early adolescence: Trend of codevelopment and directionality

Abstract: Background: Higher body mass index (BMI) and internalizing symptoms often codevelop with each other, and both of them have been widely linked to child later maladjustment. However, existing studies on the association between BMI and internalizing symptoms predominantly focus on the between-person association (i.e., the average association for a given group) and use continuous measures of BMI. To address these gaps, using approaches that can effectively partition within-person from between-person variation, thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 43 publications
(65 reference statements)
2
9
0
Order By: Relevance
“…The level of PS in children with overweight/obesity may also be affected by the opinions of outside people, their views of the image, and psychological adjustment; these extrinsic perceptions may affect weight control and alter the PS associated with overweight/obesity (74). This study also found no gender differences in the longitudinal cross-lagged relationship between PS and childhood overweight/obesity, which is consistent with findings from similar studies (41), as well as a study of BMI and internalizing symptoms from early childhood through early adolescence (37). The lack of gender differences is thought to occur after early adolescence, and studies spanning childhood, adolescence, and even adulthood may help clarify the timing and underlying mechanisms (37,60).…”
Section: Discussionsupporting
confidence: 91%
“…The level of PS in children with overweight/obesity may also be affected by the opinions of outside people, their views of the image, and psychological adjustment; these extrinsic perceptions may affect weight control and alter the PS associated with overweight/obesity (74). This study also found no gender differences in the longitudinal cross-lagged relationship between PS and childhood overweight/obesity, which is consistent with findings from similar studies (41), as well as a study of BMI and internalizing symptoms from early childhood through early adolescence (37). The lack of gender differences is thought to occur after early adolescence, and studies spanning childhood, adolescence, and even adulthood may help clarify the timing and underlying mechanisms (37,60).…”
Section: Discussionsupporting
confidence: 91%
“…We found evidence that a higher body fat percentage in low compared to high education and income groups explains part of the total disparity in internalizing symptoms. Obesity is more strongly associated with internalizing symptoms than with externalizing symptoms 38,39 , which might explain why we find contributions of differential exposure in internalizing symptoms only.…”
Section: Comparison With Previous Literaturementioning
confidence: 78%
“…While it was reported before that obesity and mental health problems more often co-occur among households with a low as compared to high SEP 10 , our study is novel in that it finds evidence for the mediating role of obesity on socioeconomic inequalities in internalizing symptoms. The fact that differential exposure to obesity might explain the socioeconomic inequality in internalizing symptoms in childhood was indirectly suggested by Zhou et al 39 and Patalay et al 40 who found an attenuation of the link between obesity and internalizing symptoms after controlling for SEP and concluded that SEP is a shared origin for both. We add to this finding by quantifying the actual contribution of differential exposure to high body fat percentage to socioeconomic inequalities in young adolescents' mental health.…”
Section: Comparison With Previous Literaturementioning
confidence: 94%
“…The value of each indicator was normalized as z-scores so that each component has a mean of 0 and a SD of 1. Finally, all the available z-scores of SES indicators were averaged to represent the score of childhood SES [ 25 ]. The higher the score was, the higher childhood SES.…”
Section: Methodsmentioning
confidence: 99%